Detection of erythromycin-resistant determinants by PCR. - Sutcliffe, J (1996)
Erythromycin resistance determinants include Erm methylases, efflux pumps, and inactivating enzymes. To distinguish the different mechanisms of resistance in clinical isolates, PCR primers were designed so that amplification of the partial gene products could be detected in multiplex PCRs. This methodology enables the direct sequencing of amplified PCR products that can be used to compare resistance determinants in clinical strains. Further, this methodology could be useful in surveillance studies of erythromycin-resistant determinants.